Red dress in black and white - Ackerman, Elliot (Alfred A. Knopf, 2020)
"The story of an American woman attempting to leave behind her life in Turkey--to leave without her husband. Catherine has been married for many years to Murat, an influential Turkish real estate developer, and they have a young son together, William. But when she decides to leave her marriage and return home to the U.S., with William and her photographer lover, Murat determines to take a stand. He enlists the help of an American diplomat to prevent his wife and child from leaving the country--but, by inviting this scrutiny into their private lives, Murat becomes only further enmeshed in a web of deception and corruption. As the hidden architecture of these relationships is gradually exposed, we learn the true nature of a cast of struggling artists, wealthy businessmen, expats and spies, a child pulled in different directions by his parents, and, ultimately, a society in crisis."--Provided by publisher.